Computable general equilibrium models : a literature review - Menezes, António Gomes de (2011)
Applied general equilibrium models have become popular tools used on ongoing economic policy debates. In this paper we discuss at length the most proeminent features of applied general equilibrium models in a comprehensive and non-technical way, thus accessible to the reader interested in economic policy but with no prior formal exposure to economic modeling. We rationalize the increasing political demand for such models as policy analysis tools. We argue that applied general equilibrium models are best equipped to model regional economies.